Evaluation of heavy metal uptake by Ricinus communis as a phythoremediator of soil contaminated with sewage sludge - Abdul Rahman, Azmi (2016)
Phytoremediation is a biological treatment that removes pollution from soil and underground water using plants as the remediation agent. The objectives of this study were; to evaluate the potential of Ricinus communis in taking up heavy metals (copper, lead and zinc) from soil contaminated with sewage sludge and translocating of heavy metals in different plants parts (leaves, stems and roots). This study was conducted in a greenhouse at the Faculty of Forestry, Universiti Putra Malaysia for six months. The seedlings of R. communis were germinated for a period of 16 weeks prior transplanting into soil containing between 0% t0 100% sewage sludge in four replications. The results showed that there is significant difference heavy metal concentrations in the growth medium and accumulation in the plant parts throughout all treatments. The Bio-concentration factor (BCF) value of heavy metals was less than 1 while translocation factor (TF) value was more than 1 indicating that R. communis is a potential phytoremediator. Future studies to identify the potential of R. communis for eliminating other heavy metals in soils contaminated with domestic and industrial sludge need to be conducted in more details.